Characterization of Cellulolytic Activities of Environmental Bacterial Consortia from an Argentinian Native Forest - Romano, Nelson Gaston; Gioffre, Andrea; Sede, Silvana Mabel; Campos, Eleonora; Cataldi, Angel Adrian; Talia, Paola Mónica (Springer, 2019)
Cellulolytic activities of three bacterial consortia derived from a forest soil sample from Chaco region, Argentina, were characterized. The phylogenetic analysis of consortia revealed two main highly supported groups including Achromobacter and Pseudomonas genera. All three consortia presented cellulolytic activity. The carboxymethylcellulase (CMCase) and total cellulase activities were studied both quantitatively and qualitatively and optimal enzymatic conditions were characterized and compared among the three consortia. Thermal and pH stability were analyzed. Based on its cellulolytic activity, one consortium was selected for further characterization by zymography. We detected a specific protein of 55 kDa with CMCase activity. In this study, we have shown that these consortia encode for cellulolytic enzymes. These enzymes could be useful for lignocellulosic biomass degradation into simple components and for different industrial applications.